1995
DOI: 10.1002/1097-4679(199505)51:3<383::aid-jclp2270510310>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional characteristics of the SCL-90-R: Evaluation of gender differences in dually diagnosed inpatients

Abstract: The dimensional characteristics of the SCL‐90‐R were assessed for both male and female dually diagnosed inpatients. Subjects included 402 males and 227 females who presented with concurrent psychiatric and substance use disorders at a private psychiatric hospital. Confirmatory factor analyses resulted in the rejection of four previous measurement models for both genders including the original nine symptom dimensions. Subsequent principal component analyses resulted in four‐ and seven‐component solutions for ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 26 publications
4
24
0
Order By: Relevance
“…They also reported high intercorrelations between the nine original dimensions, which also could suggest that the instrument is measuring one dimension. A single predominant factor was also suggested in a study using a sample of patients from a psychiatric hospital with comorbid SUD and psychiatric disorders (Carpenter & Hittner, 1995). Vassend & Skrondal (1999) concluded that different methodological strategies can produce different results; a further exploration of the original nine dimensions is therefore supported among patients with SUD.…”
Section: Introductionsupporting
confidence: 69%
“…They also reported high intercorrelations between the nine original dimensions, which also could suggest that the instrument is measuring one dimension. A single predominant factor was also suggested in a study using a sample of patients from a psychiatric hospital with comorbid SUD and psychiatric disorders (Carpenter & Hittner, 1995). Vassend & Skrondal (1999) concluded that different methodological strategies can produce different results; a further exploration of the original nine dimensions is therefore supported among patients with SUD.…”
Section: Introductionsupporting
confidence: 69%
“…Consistent with previous research [17,21,23], however, the SCL-90-R should be most appropriately viewed in this context as a more onedimensional (general) measure of psychological and symptomatic distress than a multi-dimensional one.…”
Section: Discussionmentioning
confidence: 99%
“…The Global Severity Index combines information on the total number of symptoms endorsed and the intensity of perceived distress and has been described as the single best indicator of psychological and symptomatic distress on the inventory [16]. The SCL-90-R has an extensive history within the clinical health sciences [17][18][19][20][21][22][23] and has been found to be particularly useful in discriminating symptoms related to depression and anxiety [24].…”
Section: Introductionmentioning
confidence: 99%
“…Psychological distress was assessed via a Dutch version (Arrindell and Ettema, 1986) of the Symptom Checklist -90 (SCL-90). Among the numerous self-report measures used to assess psychopathology, this SCL-90 is one that has received extensive clinical use, and has been the focus of much research interest (Carpenter and Hittner, 1995). Ratings were requested for eight different symptom groups: anxiety, agoraphobia, depression, somatic complaints, insufficiency of thinking and behaviour, interpersonal sensitivity, hostility, and sleeping problems.…”
Section: Methodsmentioning
confidence: 94%